Systematic Literature Reviews: The Effectiveness of Social-Emotional Learning Interventions for Elementary School Students and Teachers - Oktoriyadi,; Aunurrahman,; Sulistyarini,; Agung Hartoyo,; Ahmad Yani T, (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
This systematic review aims to analyze the effectiveness of Social Emotional Learning (SEL) interventions for elementary school students and teachers. Articles were searched through ScienceDirect following the PRISMA guidelines with a publication range of 2021–2025. Of the 411 articles identified with the keywords “Social Emotional Learning (SEL) Interventions for Elementary School Students,” 15 articles met the inclusion criteria. The results of a systematic review of fifteen articles show that Social Emotional Learning (SEL) research in elementary schools focuses on three main areas: SEL program interventions, measurement of social-emotional competencies, and the role of teachers and parents in SEL implementation. Seven intervention studies reported positive results, such as the ReadySET program, which improved the comfort level of SEL practices; the well-being diary, which improved student well-being; Tools for Getting Along, which strengthened executive functions; The Nous Project, which improved the relational climate; the PATH program, which was trauma-sensitive for at-risk students; and the use of S.S. GRIN technology, which improved SEL competencies. In terms of measurement, DESSA-Mini showed a pattern of improvement in social-emotional competencies, the multilevel model identified variations in development among students, and SERA offered a valid measure of emotion regulation. Studies on the role of teachers and the social environment revealed that teachers' SEL skills were related to students' empathy and prosocial behavior, while A+ online training improved teachers' emotional well-being. Overall, the effectiveness of SEL depends on the quality of interventions, robust measurement, and teacher and parent support. Therefore, future SEL research requires sustainable, cross-cultural intervention models and a school ecosystem oriented toward ensuring the effectiveness of social-emotional learning at the elementary school level